FACTORS AFFECTING THE ROAD SAFETY (Perner's Contacts, 2015)
This paper deals with the issue of road safety and with factors affecting the road safety. The factors are divided into three groups: driver behaviour, construction and condition of the vehicle and condition of infrastructure. The paper also deals with the issue of alcohol that also has influence on the road safety.
Keywords: road safety, driver, accident